Perancangan Antena Pesawat Tanpa Awak Menggunakan ANSYS High-Frequency Structure Simulator - Ruliyanta Ruliyanta; Muhammad Fahrurozi; Herry Satria Utama (Jurnal Ilmiah Giga, 2022)
Using crewless aircraft or Unmanned Aerial vehicles (UAV) is rife in the civil and military world. The problem that often occurs is that the UAV has disconnected from the control center. One of the reasons was that the aircraft was operating outside the radio control center's range. This study aims to design a control antenna with a higher gain than the previous research antenna, which is used as a reference. The method we used is designing a 2×8 circular array microstrip antenna using the Ansys high-frequency structure simulator (HFSS) software. The result gives a return loss value of -30.25 dB, a voltage standing wave ratio (VSWR) of 1.11, and a bandwidth of 512,1 MHz. The amount of gain is 12.94 dB. The magnitude of the reflection coefficient of the designed antenna is 0.017. This value means that the amount of power reflected by the designed antenna is 1.7%, or the antenna is capable of capturing signals of up to 98.3%.